Distributed cross-layer coordination of congestion control and resource allocation in S-TDMA wireless networks - Soldati, Pablo; Johansson, Björn; Johansson, Mikael (Wireless networks, 2008)
We consider the problem of joint congestion control and resource allocation in spatial-TDMA wireless networks. The design problem is posed as a utility maximization problem subject to link rate constraints which involve both transmission scheduling and power allocation. Starting from the performance limitations of a centralized optimization based on global network information, we proceed systematically in our development of two distributed and transparent protocols that rely on local information only. In the process, we introduce a novel decomposition method for convex optimization, establish its convergence for the utility maximization problem, and demonstrate how it suggests a distributed solution based on TCP/AQM and incremental updates of the transmission schedule. We develop a two-step procedure for finding the schedule updates and suggest two schemes for distributed link scheduling and power control under realistic interference models. Although the final protocols are suboptimal, we isolate and quantify the performance losses incurred by each simplification and demonstrate strong performance in examples.